2017
DOI: 10.17221/96/2016-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid levels in muscle tissue of eight meat cattle breeds

Abstract: Vopálenský J., Suchý P., Straková E., Šimek F., Macháček M., Herzig I. (2017): Amino acid levels in muscle tissue of eight meat cattle breeds. Czech J. Anim. Sci., 62, 339-346.Ten clinically healthy bulls equal in weight were chosen from eight meat cattle breeds maintained in the same geographical conditions using the extensive grazing method. After slaughtering, muscle tissue samples were taken from the musculus longissimus and pars thoracis, and dry matter, nitrogenous substances, fat, and the levels of esse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
3
4
1
Order By: Relevance
“…Glutamic and aspartic acid, alanine, lysine and leucine are the most abundant amino acids in game meat [52], and this corresponds to the results of this study. Non-essential amino acids (g/100 g meat) found in axis meat had a similar content to those reported by Lorenzo et al [13] in wild red deer and by Hoffman et al [53] in springbok meat. Analysing amino acid content in five ungulate game species (wild and farmed deer, roe deer, elk, wild boar), Strazdina et al [5] reported a lower content of major non-essential amino acids than found in this study.…”
Section: Amino Acid Contentsupporting
confidence: 86%
See 3 more Smart Citations
“…Glutamic and aspartic acid, alanine, lysine and leucine are the most abundant amino acids in game meat [52], and this corresponds to the results of this study. Non-essential amino acids (g/100 g meat) found in axis meat had a similar content to those reported by Lorenzo et al [13] in wild red deer and by Hoffman et al [53] in springbok meat. Analysing amino acid content in five ungulate game species (wild and farmed deer, roe deer, elk, wild boar), Strazdina et al [5] reported a lower content of major non-essential amino acids than found in this study.…”
Section: Amino Acid Contentsupporting
confidence: 86%
“…The nutritional value of meat protein depends on the presence or absence of non-essential and essential amino acids. As in the present study, a minor effect of sex and age on amino acid content was reported for red deer and springbok [13,53]. Cygan-Szczegielniak and Janicki [8] also reported a minor effect of sex on non-essential amino acids in roe deer meat, but a significant effect of essential amino acid content.…”
Section: Amino Acid Contentsupporting
confidence: 76%
See 2 more Smart Citations
“…Arg, Leu, and Lys were the most frequent amino acids in the EAA group, and Glu and Asp were the most frequent amino acids in the NEAA group. Comparison of amino acid profiles between the meat of F. limosus and livestock [ 41 , 66 , 67 , 68 ] and fish [ 69 , 70 , 71 ] showed that raw material collected from spiny-cheek crayfish has similar or higher free amino acid concentrations (Arg, Ile, Leu, Trp, Glu) than that from vertebrates. According to Claybrook [ 72 ], this is a manifestation of differing osmoregulatory needs.…”
Section: Resultsmentioning
confidence: 99%